Curriculum for diagnostic endoscopic ultrasound training in Europe: European Society of Gastrointestinal Endoscopy (ESGE) Position Statement - Badaoui, Abdenor; Teles de Campos, Sara; Fusaroli, Pietro; Gincul, Rodica; Kahaleh, Michel; Poley, Jan-Werner; Sosa Valencia, Leonardo; Czako, Laszlo; Gines, Angels; Hucl, Tomas; Kalaitzakis, Evangelos; Petrone, Maria Chiara; et al. (Endoscopy, 2024)
The European Society of Gastrointestinal Endoscopy (ESGE) has recognized the need to formalize and enhance training in diagnostic endoscopic ultrasound (EUS). This manuscript represents the outcome of a formal Delphi process resulting in an official Position Statement of the ESGE and provides a framework to develop and maintain skills in diagnostic EUS. This curriculum is set out in terms of the prerequisites prior to training; the recommended steps of training to a defined syllabus; the quality of training; and how competence should be defined and evidenced before independent practice. 1: Trainees should have achieved competence in upper gastrointestinal endoscopy before training in diagnostic EUS. 2: The development of diagnostic EUS skills by methods that do not involve patients is advisable, but not mandatory, prior to commencing formal training in diagnostic EUS. 3: A trainee's principal trainer should be performing adequate volumes of diagnostic EUSs to demonstrate maintenance of their own competence. 4: Training centers for diagnostic EUS should offer expertise, as well as a high volume of procedures per year, to ensure an optimal level of quality for training. Under these conditions, training centers should be able to provide trainees with a sufficient wealth of experience in diagnostic EUS for at least 12 months. 5: Trainees should engage in formal training and supplement this with a range of learning resources for diagnostic EUS, including EUS-guided fine-needle aspiration and biopsy (FNA/FNB). 6: EUS training should follow a structured syllabus to guide the learning program. 7: A minimum procedure volume should be offered to trainees during diagnostic EUS training to ensure that they have the opportunity to achieve competence in the technique. To evaluate competence in diagnostic EUS, trainees should have completed a minimum of 250 supervised EUS procedures: 80 for luminal tumors, 20 for subepithelial lesions, and 150 for pancreaticobiliary lesions. At least 75 EUS-FNA/FNBs should be performed, including mostly pancreaticobiliary lesions. 8: Competence assessment in diagnostic EUS should take into consideration not only technical skills, but also cognitive and integrative skills. A reliable valid assessment tool should be used regularly during diagnostic EUS training to track the acquisition of competence and to support trainee feedback. 9: A period of supervised practice should follow the start of independent activity. Supervision can be delivered either on site if other colleagues are already practicing EUS or by maintaining contacts with the training center and/or other EUS experts. 10: Key performance measures including the annual number of procedures, frequency of obtaining a diagnostic sample during EUS-FNA/FNB, and adverse events should be recorded within an electronic documentation system and evaluated.
Keywords: Endosonography; kurikulum; biopsie tenkou jehlou pod endosonografickou kontrolou; Curriculum; endosonografie; Humans; Endoscopic Ultrasound-Guided Fine Needle Aspiration; lidé; gastrointestinální endoskopie; Endoscopy, Gastrointestinal; Europe; Evropa